2019
DOI: 10.1021/acs.jpca.9b10021
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Transitions of HOC+ Induced by Collision with He at Low Temperatures

Abstract: The HOC + molecule has for long been detected in several regions of the interstellar medium (ISM). The collisional ro-vibrational rate coefficients of this molecule with the most common colliders in the ISM are then required for applying nonlocal thermal equilibrium models. However, this molecule has a low bending frequency (249 cm −1 ), and the use of the rigid rotor approximation is therefore limited to low collision energies. Also, the complete determination of the ro-vibrational rate coefficients of HOC + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 34 publications
5
6
0
Order By: Relevance
“…The comparison of present results with that of HCO + -He 12,17 shows that both isomers have comparable rate (∼ 10 −10 cm 3 molecule −1 s −1 ) and similar behaviour. We have also compared our rate coefficients data with Santander et al 34 in the Figure 5 (right panel), and our data is found to be in the same order with very negligible differences as evident from the Table 5. The small differences are suspected to be due to different welldepth values and different procedures of analytical fitting.…”
Section: Rate Coefficientssupporting
confidence: 70%
See 3 more Smart Citations
“…The comparison of present results with that of HCO + -He 12,17 shows that both isomers have comparable rate (∼ 10 −10 cm 3 molecule −1 s −1 ) and similar behaviour. We have also compared our rate coefficients data with Santander et al 34 in the Figure 5 (right panel), and our data is found to be in the same order with very negligible differences as evident from the Table 5. The small differences are suspected to be due to different welldepth values and different procedures of analytical fitting.…”
Section: Rate Coefficientssupporting
confidence: 70%
“…Cross-sections for 1→0 transitions predominate over 2→0 and 3→0. When compared to recent data of cross-sections of COH + -He 34 , the results are found to be approximately same. The small differences observed may be because of difference in reported well-depth values or B e value that they took into consideration.…”
Section: State-to-state and Pressure Broadening Cross-sectionssupporting
confidence: 62%
See 2 more Smart Citations
“…10 2 10 4 10 6 10 8 20 40 10 2 10 4 10 6 10 8 10 2 10 4 10 6 10 8 0.0 0. (Santander et al 2019) have been reported over the last decades. In all these studies, differences ranging from few tenths of a percent up to one order of magnitude were found.…”
Section: Resultsmentioning
confidence: 99%